Ichthyosaurs [book with audioplayer] - Moening, Kate (Moening, Kate. Ancient marine life., 2024)
"The biggest Ichthyosaurs grew up to 85 feet long. They were as long as three school buses! Readers will learn this and more in this fact-filled title. Leveled text and colorful illustrations highlight the animal’s body parts, favorite meals, common behaviors, and extinction. Special features include a size comparison, a diet graphic, a map of where a notable fossil was found, and more. The book ends with a full-spread profile that puts important information about Ichthyosaurs in one place!" --